2014
DOI: 10.1093/jnci/djt430
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Lycopene, Angiogenesis, and Prostate Cancer: A Prospective Study in the Prostate-Specific Antigen Era

Abstract: Dietary intake of lycopene was associated with reduced risk of lethal prostate cancer and with a lesser degree of angiogenesis in the tumor. Because angiogenesis is a strong progression factor, an endpoint of lethal prostate cancer may be more relevant than an endpoint of indolent prostate cancer for lycopene in the era of highly prevalent prostate-specific antigen screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
140
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(147 citation statements)
references
References 40 publications
3
140
0
4
Order By: Relevance
“…Lycopene, the predominant carotenoid found in tomatoes, has been widely investigated for its effects in PCa. Lycopene has been demonstrated to modulate growth factor signaling, cell-cycle programming, angiogenesis, and apoptosis in PCa cell lines [3][4][5][6][7][8][9]. Numerous epidemiology studies have examined the effects of lycopene and tomato products on PCa risk [2, 7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Lycopene, the predominant carotenoid found in tomatoes, has been widely investigated for its effects in PCa. Lycopene has been demonstrated to modulate growth factor signaling, cell-cycle programming, angiogenesis, and apoptosis in PCa cell lines [3][4][5][6][7][8][9]. Numerous epidemiology studies have examined the effects of lycopene and tomato products on PCa risk [2, 7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Our results are consistent with studies that suggest dietary and circulating lycopene has stronger inverse associations with risk of lethal or aggressive diseases. 16,32 One plausible explanation is that low-grade tumors that progress slowly may not be sensitive to effects of lycopene, while high-grade tumors that progress rapidly are more susceptible to inhibition by lycopene. In addition, an average of 10 years of follow-up may not be long enough to observe an association for low-grade tumors, relatively few of which are fatal within 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Higher lycopene dietary intake was inversely associated with total prostate cancer and with angiogenic potential, suggesting a reduction of the aggressive potential of prostate cancer (Zu et al, 2014). The use of lycopene extracts as a supplement has been compared to the consumption of lycopene in the form of whole food sources, and it has been concluded that in the case of cardiovascular risk factors, tomato intake was more favorable with the exception of blood pressure management (Burton-Freeman and Sesso, 2014).…”
Section: Introductionmentioning
confidence: 99%